The Influence of Self-Assessment System, Tax Knowledge, Love of Money, and Compliance Costs on Tax Evasion with Tax Incentives as a Moderating Variable for MSME Taxpayers - Ustantini, Sinta; Prihatiningtias, Yeney Widya; Djamhuri, Ali (Universitas Pendidikan Ganesha, 2024)
This study aims to examine the influence of the Self-Assessment System, Tax Knowledge, Love of Money, and Compliance Costs on Tax Evasion with Tax Incentives as a Moderating Variable for MSME Taxpayers. The Theory of Planned Behavior is used as the theoretical framework in this research. This study utilizes primary data, and the sample is selected using purposive sampling, resulting in a sample from 150 respondents. The research employs quantitative data analysis with multiple linear regression and moderated regression analysis methods. The results of the study indicate that the Self-Assessment System, Love of Money, and Compliance Costs significantly increase tax evasion, while Tax Knowledge reduces tax evasion. Additionally, the presence of tax incentives has a significant impact on tax evasion behavior among MSMEs. Properly regulated tax incentives can be an effective tool to moderate and reduce tax evasion .